OPTIMIZING THE MANAGEMENT OF MARINE TOURISM POTENTIAL IN SIMEULUE DISTRICT - Ikbal, Aria (Journal of Political and Governance Studies, 2025)
Background Tourism management has developed into one of the largest industries for economic growth in Indonesia. This research focuses on optimizing the management of marine tourism potential in Simeulue Regency, especially on Alaek Sektare beach in Lantik Village. The study aims to find out how to optimize the management of marine tourism potential as well as obstacles in optimizing the management of marine tourism potential in Simeulue Regency. Methods The method used is a qualitative method with a descriptive approach, and the determination of informants in the research is carried out by purposive sampling techniques, namely the Tourism Office, Inaugural Village Apparatus, Business Managers, Business Actors, and the community. Observation, interviews, and documentation were collected data techniques in the study, then the data was analyzed in three stages, namely reduction, display, and conclusion verification. Results The results of this study show that efforts to optimize the management of marine tourism potential in Simeulue Regency are carried out with a management process that involves planning, organizing, mobilizing, and supervising/controlling. Conclusions The study concludes that the implementation of the management of beach tourism potential in Simeulue Regency by the Tourism Office and the Lantik Village Government has gone well. Optimizing the management of Alaek Sektare beach tourism has not achieved maximum results. This is due to several factors that hinder the optimization of management in terms of low quality of human resources, limited budget, imbalance between the construction of tourism facilities, and other factors, namely the reorientation of budget distribution priorities